2011
DOI: 10.1089/jwh.2010.2429
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Updated Institute of Medicine Guidelines on Prepregnancy Body Mass Index Categorization, Gestational Weight Gain Recommendations, and Needed Counseling

Abstract: Changes in IOM GWG recommendations alter gravidas' BMI categories and, thus, the recommended GWG. As the amount advised is associated with actual gain, accuracy is paramount. GWG is a modifiable parameter associated with immediate and long-term maternal/neonatal health outcomes, and counseling can have a significant public health impact and should involve BMI determination, followed by BMI-specific GWG recommendations in accordance with current guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 46 publications
3
47
1
Order By: Relevance
“…Our population-based frequencies were similar to those from hospital-based data from Central Massachusetts [5] that shows 16.7%, 30.8%, and 52.6% were under-gainers, appropriate gainers, and over-gainers, respectively. The overall proportion of appropriate gainers in our population is in accordance with that reported by the IOM in the US population [6] although the frequency of obese in the American population of pregnant mothers is twice that of Slovenian women.…”
Section: Discussionsupporting
confidence: 78%
“…Our population-based frequencies were similar to those from hospital-based data from Central Massachusetts [5] that shows 16.7%, 30.8%, and 52.6% were under-gainers, appropriate gainers, and over-gainers, respectively. The overall proportion of appropriate gainers in our population is in accordance with that reported by the IOM in the US population [6] although the frequency of obese in the American population of pregnant mothers is twice that of Slovenian women.…”
Section: Discussionsupporting
confidence: 78%
“…33 Simas and colleagues reported that 44% of normal weight women, 69% of overweight women, and 60% of obese women in their sample gained in excess of the guidelines. Discrepancies in the rates observed in that study and in the current report may be explained by differences in the samples examined; specifically, Simas and colleagues had over double the number of women self-identifying as Hispanic, and our results suggest that fewer gestational weight gain excursions may be seen within this group.…”
Section: Discussionmentioning
confidence: 98%
“…16 Obstetrical practice is changing to address these guidelines, and data suggest that meeting IOM guidelines does improve pregnancy outcomes. [16][17][18][19] Changes in obstetrical practice may also influence offspring growth patterns. However the influence of obstetrical changes on pediatric outcomes remains largely unexamined.…”
Section: Introductionmentioning
confidence: 99%